STUDY OF THE INFLUENCE OF EMOTIONAL INTELLIGENCE UPON SPORT PERFORMANCE OF GYMNASTS - Ramona Ancuţa NUŢ (Cluj University Press, 2015)
Trainers and parents have always been interested in sport achievement and children's emotional adaptation both inside and outside of the official framework provided by a sport club. However, in the last period, the researchers found out that the child's emotional life has a significant impact on the aforesaid two aspects. Thus, the Emotional Intelligence has become an important area of research in the field of human resources, management, sport and psychology. Goleman (1995) believes that development of the students' emotional aptitudes is as important as the development of their cognitive abilities, therefore the EI concept has the same importance as the well known IQ. Moreover, the latest studies show that the IE predicts in a proportion of 80% the achievements of a person during the lifetime. The topic of this research consists in the study of the importance of emotional intelligence for sport performance of gymnasts. The research starts from the fact that certain individuals have outstanding results in practice and succeed better in life than others who have a greater (cognitive) IQ. Studiu cu privire la influența inteligenței emoționale asupra performanței sportive a gimnaștilor. Antrenorii şi părinții au fost mereu interesaţi de succesul sportiv şi de adaptarea emoțională a copiilor, atât în cadrul formal oferit de clubul sportiv cât şi în afara acestuia. Însă, doar în ultimul timp, cercetătorii au realizat că viaţa emoţională a copilului are un impact semnificativ asupra celor două aspecte amintite. Astfel, Inteligenţa emoţională a devenit un câmp important de cercetări în domeniul resurselor umane, management, sport şi psihologie. Goleman (1995) susţine că dezvoltarea aptitudinilor emoţionale ale elevilor este la fel de vitală ca dezvoltarea abilităţilor lor cognitive, astfel că IE este un concept la fel de important ca mult mai familiarul IQ. Mai mult, studiile recente au demonstrat faptul că IE prezice aproximativ 80% din succesul unei persoane în viaţă. Tema acestei cercetări o reprezintă studiul asupra importanţei inteligenţei emoţionale în performanţa sportivă a gimnastelor. Cercetarea porneşte de la adevărul cuprins în afirmaţiile referitoare la faptul că anumite persoane au rezultate deosebite în practică şi reuşesc mai bine în viaţă decât altele, care au un IQ (cognitiv) mai mare.  Cuvinte cheie: performanță sportivă, inteligență emoțională